Athlete and staff perceptions of the attributes athletes require to be ready for team selection in Australian football - Turner, C.; Vickery, W.; Dingeldei, L.; Dwyer, D. B.; Bruce, L. (International Journal of Sports Science & Coaching, 2025)
A notable amount of research in Australian Football describes what separates drafted from non-drafted athletes, however there is limited understanding of how Australian Football League (AFL) listed athletes, progress into the weekly AFL team. This study aimed to understand the perceptions of club staff and elite athletes on what attributes are needed for an athlete to be considered `ready` for selection in the AFL. Semi-structured interviews were conducted with 12 staff members and nine athletes from one AFL club. The specific attributes required by athletes depend on their playing position. Staff generally agreed on the importance of physical and physiological, and technical and tactical attributes, while psychological and performance attributes were also considered in the assesment of readiness. Athletes indicated they needed to possess the psychological, physical, technical, and tactical skills required before they were considered ready. Staff and athletes suggested that to achieve these attributes, athletes needed to be healthy and injury free. Findings suggest that two categories of attributes may exist in the assessment of readiness, the first consisting of attributes considered essential and possessed by a larger portion of athletes, while the second consists of attributes seen as less essential but more impactful to performance. These novel insights provide agreement across the football department about what determines player readiness, in order provide an aligned interdisciplinary approach to developing athletes. Findings also have the potential to benefit playing groups across the league, giving athletes greater clarity of what is expected of them to be considered ready for selection into an AFL team.